Intercollegiate Rodeo, March 22 and 23 - Uribes, Tom::::::::: (2013)
The Fresno State Intercollegiate Rodeo will feature college cowboys and cowgirls from throughout the West Coast region including Bulldogger Uhuru Adem, who is currently sitting in first place in the Saddle Bronco riding, and angling for a shot at the College National Finals Rodeo in June.